A Short Review on Raman Studies of Metal Chalcogenide Semiconductor Thin Films - Ho, S.M.; Othman, M.H.D.; Adam, M.R.; Mohanraj, K. (Asian Journal of Chemistry, 2021)
The productions of the thin metallic chalcogenide films are of particular interest for the wide range of fabrication of the solar cells, sensors, photodiode arrays, photoconductors. Raman spectroscopy is used to measure the scattering radiation of a matter. Basically, the spectroscopic methods can be defined as the study of the interaction of electromagnetic radiation with a matter. It can be based on the phenomenon of absorption, fluorescence, emission or scattering. The observation of peaks supported the formation of amorphous or crystalline nature of the samples. In this short review, the authors had gathered some informations about the Raman studies of recently synthesized metal chalcogenide semiconductor thin films.